Comparison Analysis of Wind Patterns and Its Correlations to Temperature, Humidity and Rainfall in Coastal and Non-Coastal Areas - Aqasha Raechan Anam; Fikri Asfahanif; Veyqah Dwi Muthi'ah; Alfi Dimas Pangedoan; Giarno Giarno (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Geographical location and topography determine the characteristics of atmospheric parameters in a location. This study aims to determine the comparison between wind patterns that occur in coastal and non-coastal areas, then the correlation between wind patterns and parameters of temperature, humidity and rainfall that occur at the Tanjung Priok Maritime Station and the Curug Meteorological Station. The chosen research method is descriptive analysis. This result is analysis of hourly wind data at the Tanjung Priok Maritime Station is dominated by local winds or sea breezes while the Curug Station is dominated by monsoon winds. The dominant wind direction in the months of the transitional season has a smaller percentage than in other months. Furthermore, the rainfall is dominated by rainfall from the west in the seasonal pattern as well as the humidity parameters at the two research stations. Temperatures in coastal areas as a whole are higher than non-coastal temperatures with a difference of up to 3 degrees Celsius. Last, in the temperature trend there is a random distribution pattern at the Curug meteorological station and there is no trend at the Tanjung Priok Maritime Station. The largest temperature is the same in 2019 and the average temperature is 0.3/year.